Intraindividual comparison of selective intraarterial versus systemic intravenous 68Ga-DOTATATE PET/CT in patients with inoperable meningioma - Verburg, Frederik A.; Wiessmann, Martin; Neuloh, Georg; Mottaghy, Felix M.; Brockmann, Marc-Alexander (Nuklearmedizin - NuclearMedicine, 2019)
Aim Here we describe the results of superselective intraarterial application of diagnostic Ga-68-DOTA0,Tyr3-octreotate (Ga-68-DOTATATE) in a series of patients with inoperable WHO grade II meningiomas which were no longer amenable to radiotherapy.Methods Four patients with inoperable WHO grade II meningioma underwent systemic venous infusion of Ga-68-DOTATATE followed by PET/CT. Ga-68-DOTATATE application was repeated intraarterially via transfemoral catheterization of vessels supplying the meningioma and another PET/CT was performed.Results Selective arterial infusion of Ga-68-DOTATATE increased the median value for the maximum standardized uptake value (SUV) by 2.6-fold (median venous: 7.1, median arterial: 21.6; range 2.0–5.0) and the median value for mean SUV by 2.7-fold (median venous: 4.3, median arterial: 11.2; range 1.6–5.6) compared to systemic intravenous infusion. Arterial application was well tolerated by all patients without complications. When compared to liver uptake, intravenous tracer uptake was insufficient for PRRT, whereas tracer uptake after superselective intraarterial tracer injection was sufficient to allow for peptide receptor radionuclide therapy (PRRT) in all patients.Conclusion Insufficient tracer uptake in meningiomas after intravenous application of Ga-68-DOTATATE may be safely increased by a factor of 2–5 using transfemoral selective intraarterial tracer application.
Keywords: Meningioma; somatostatin receptor; radionuclide therapy; arterial application